Advanced numerical analyses by the Non‐Smooth Contact Dynamics method of an ancient masonry bell tower. (7th February 2020) - Ferrante, Angela; Clementi, Francesco; Milani, Gabriele
Abstract : Advanced numerical analyses were carried out in order to assess the nonlinear dynamical behaviour of the bell tower of Pomposa Abbey in Codigoro, in the province of Ferrara (Italy), by means of the Non‐Smooth Contact Dynamics (NSCD) method. The main purpose of the work is to investigate the capacity of the main mechanical parameter used in the analyses, namely, the friction coefficient, to have effects on the mechanical response of ancient masonry structures undergoing seismic actions. Therefore, the tower was modelled following the discrete element method (DEM) and assembling the masonry texture as rigid bodies tied by frictional joints. Thus a discontinuous approach was used to assess the dynamic properties and the vulnerability of the masonry structure, through large deformations regulated by the Signorini's law, concerning the impenetrability between the rigid bodies; and by the Coulomb's law, regarding the dry‐friction model. Afterward, different values were assigned to the friction coefficient of the models, and a variety of real seismic shocks have been applied in the nonlinear analyses. Finally, it is possible to see different failure mechanisms resulting for each friction value and types of dynamic actions used, as expected.